Issues of rearrangement of road interchange exits for the traffic safety - O. S. Matigorova; R. V. Andronov (Архитектура, строительство, транспорт)
The article describes the possibility of modernization of one of the common types of interchanges at different levels in our country named "cloverleaf". It's important because the zones of interlacing flows of loop exits with a significant traffic intensity re duces the sa fety of tr affic along them and the overall throughput of the interchange. This study simulates the operation of an interchange with a left-turn semi-direct ramp at different levels on the busiest left-turn direction of traffic.   The aim of the article is to show the significant effectiveness of this design solution.